Қазақ мәдениетіндегі «сән» ұғымының қалыптасуы мен дамуының этномәдени сипаты (Eurasian Journal of Philology Science and Education, 2018)
The ethnocultural description of the formation and development of the concept of «fashion» in Kazakh culture is presented in the article. It is traced how the concept of «fashion» is revealed in ethnolinguisms representing the ethnic originality of the Kazakh people.In the course of research of the diachronicand synchronous state of the study of the concept of «fashion» in Kazakh culture, the author makes anattempt to conduct an experiment in public environment, the results of which have been analyzed anddescribed in this article. From the scientific point of view, it is evidenced and described how the concept of «fashion» evolved parallel with the formation and development of the ethnos and found its directreflection in words and deeds, in appearance and character,in culture and behavior,as well as in products and household items the names of which are embodied in ethnolinguismsexposed to changes inthe process of intergenerational transmission.Particular attention is paid to the influence of the conceptof «fashion» on different manifestations of Kazakh culture: a nomadic way of life, a spatial image of theworld, an ancient religious and cultural worldview that is reflected in the cognitive sphere. In the processof questioning, it is revealed that ethno-cultural names related to Kazakh folk craft became a passivereserve, and now their meanings have become distorted.Key words: fashion, customsandtraditions, ethnolingu